RANCANG BANGUN RUMAH PINTAR DENGAN PLATFORM HOME ASSISTANT BERBASIS RASPBERRY PI 3 - dany pratmanto; fandhilah fandhilah; Safuan Adi Saputra (Universitas Bina Sarana Informatika, 2019)
Abstract - The construction of this Home Automation System uses the concept of the Internet of things as architecture. Home Assistant is a Home Automation platform that is in line with the concept of the Internet of things. By using the Home Assistant framewok, the construction of home automation is easier because there is no need to make server applications and controlling applications. The results of research on the development of Home Automation Systems, namely homeowners can control their home lighting systems, live broadcasts of the state of the house with surveillance cameras, monitoring room temperature, and door locks. All that we can control through the local network and the internet.Keywords— smart home, cloud computing, internet of things (iot), raspberry pi, surveillance camerasAbstrak - Pembangunan Home Automation System ini menggunakan konsep Internet of things sebagai arsitektur. Home Assistant adalah platform Home Automation yang sesuai dengan konsep Internet of things, dengan menggunakan framewok Home Assistant maka pembangunan home automation menjadi lebih mudah karena tidak perlu membuat aplikasi server dan aplikasi pengendali. Hasil dari penelitian pembangunan Home Automation System, yaitu pemilik rumah dapat mengendalikan sistem pencahayaan rumahnya, siaran langsung keadaan rumah dengan kamera pengintai, pemantauan suhu ruangan, dan pengunci pintu. Semua itu dapat kita kendalikan melalui jaringan lokal maupun internet.Kata kunci— rumah pintar, cloud computing, internet of things (iot), raspberry pi, kamera pengintai